PELATIHAN DIGITAL MARKETING BAGI PELAKU EKONOMI KREATIF KABUPATEN KLATEN - -, Hariningsih; Istiyanto, Joko; Daryanto, Tri; Mardani, Danis Aditya; Affandi, Ridwan (Abdi Masya, 2024)
Nowadays, UMKM is required to face business challenges by adapting and innovating to survive by transforming into the digital realm. This is due to the development of information technology; most people often spend their time surfing the internet with their gadgets. There has even been a change in shopping culture from conventional to online. Online sales are not only through e-commerce or marketplaces. Now online sales have spread to social media. Entrepreneurs must have the skills to utilize technology to expand the market and increase sales. Therefore, in this community service activity, digital marketing training was carried out for creative economy entrepreneurs in Klaten Regency to help expand the market and increase sales through digital marketing. The materials that will be provided are the concept of marketing content, the use of e-commerce applications, and digital marketing through social media. The success of the training was evaluated using the Likert scale method. The knowledge of the training participants increased after attending the training. The post-test results showed an average of 83.22%, while the previous pre-test was only 58.77%. The evaluation results showed that participants were satisfied with the training that had been held, with a satisfaction level of 83.01%.